Explaining the Relationship between - Ghodrat Zare Andarian; Hossein Zabihi; saeid kardar (تحقیقات کاربردی علوم جغرافیایی)
Citizenship is a set of rights and duties a citizen enjoys because of his or her country of residence. Municipal law is a set of laws, rules and regulations that govern the interconnection of citizens and city departments in local and urban affairs, and explain the duties of overseers of councils, municipalities, and other city institutions; And planners 'and architects' awareness of the rights of citizens is one of the influential components in the process of urban architecture planning which is discussed in this article. Contemporary theories of urban law have led to a new military framework based on the concept of "right to the city" about urban life; if general framework can be understood in the context of the general concept of "right to the city", the following formulation from the Eiken set of laws on the concept of citizenship. It provided the architectural and urban planning rights: 1. the right to allocate; 2. the right to participate; 3. the right to centralization; Right of residence The right to habitation; 6. The right to individualization in socialization. Finally, the relationship between these components and their characteristics with the degree of their relevance and relationship with architectural and urban rights is presented.